Internet Sebagai Media Penyebaran Ideologi Radikal: Dampak, Tantangan, dan Upaya Penanggulangannya - Sholihin, Ahmad; Kurnia, Heri (Universitas Cokroaminoto Yogyakarta, 2023)
The concept of the Internet has become a very influential medium in spreading radical ideology around the world. This phenomenon has created significant social, political and security impacts in various countries. In this scientific work, we investigate the impact of the spread of radical ideology via the internet, the challenges faced in dealing with it, and the efforts made to overcome this problem. This research is based on a literature review and data analysis related to the internet as the main medium for spreading radical ideology. The challenges in dealing with the spread of radical ideology through the internet are complex and varied. Some of the main challenges include the lack of effective regulation, online anonymity, the rapid development of technology, and the existence of radical groups that are savvy in leveraging social media and online platforms to spread their message. Apart from that, there are also issues around privacy and freedom of speech that need to be maintained so they are not disturbed by countermeasures. To overcome this problem, various countermeasures have been carried out at the national and international levels. This includes establishing policies and regulations that limit the spread of radical ideologies, cooperation between governments, the technology industry, and international institutions, developing harmful content detection algorithms and technologies, and empowering people to understand and deal with radical narratives. Although countermeasures have been taken, challenges in dealing with the spread of radical ideology via the internet remain. In this scientific paper, we provide a comprehensive description of the negative impacts generated by the spread of radical ideology via the internet, the associated challenges, and the various countermeasures that have been undertaken. This research is expected to be the basis for the development of more effective strategies in dealing with this problem in the future.